Photodegradation property and antimicrobial activity of zinc oxide nanorod-coated polypropylene nonwoven fabric. (August 2021) - Zhang, Guangyu; Cheng, Ran; Yan, Jiawei; Xiao, Yao; Zang, Chuanfeng; Zhang, Yu
Abstract: Zinc oxide (ZnO) nanorods were grown on the surface of a polypropylene (PP) nonwoven fabric (NWF) using the low-temperature hydrothermal method. The finishing process was investigated, and the prepared PP NWF was characterized. Results of the scanning electron microscopy, Fourier transform infrared spectroscopy, X-ray diffraction, anti-ultraviolet (UV) properties, and energy dispersive spectrometry indicate that the ZnO nanorods can be synthesized and uniformly coated on the surface of the PP NWF. The UV-degradation behavior and antibacterial activity of 0.025 M zinc nitrate hexahydrate-treated PP NWFs was good, with an ultraviolet protection factor value exceeding 100. Furthermore, the ZnO nanorods can inhibit the photodegradation of PP NWF. No obvious cracks were found on the fiber surface under 72 h of UV-light irradiation. The longitudinal and cross-breaking strength reduction properties were enhanced substantially. The ZnO nanorod-coated PP NWF achieved 99.5% bacterial reduction of Staphylococcus aureus and 99.9% bacterial reduction of Escherichia coli. Highlights: ZnO nanorods were evenly distributed on the polypropylene nonwoven fabric surface with average diameter of 100-200nm. The prepared fabric has good anti-ultraviolet and properties, with UPF value more than 100+. Compared with control sample, mechanical properties of the ZnO-PP fabric changed little under UV radiation conditons. The amino and ZnO nanorosds has synergia antibacterial activity against Staphylococcus aureus and Escherichia coli.